Genome wide identification and experimental validation of Pseudomonas aeruginosa Tat substrates - Gimenez, Maxime Rémi (Sci Rep, 2018)
In bacteria, the twin-arginine translocation (Tat) pathway allows the export of folded proteins through the inner membrane. Proteins targeted to this system are synthesized with N-terminal signal peptides bearing a conserved twin-arginine motif. The Tat pathway is critical for many bacterial processes including pathogenesis and virulence. However, the full set of Tat substrates is unknown in many bacteria, and the reliability of in silico prediction methods largely uncertain. In this work, we performed a combination of in silico analysis and experimental validation to identify a core set of Tat substrates in the opportunistic pathogen Pseudomonas aeruginosa. In silico analysis predicted 44 putative Tat signal peptides in the P. aeruginosa PA14 proteome. We developed an improved amidase-based Tat reporter assay to show that 33 of these are real Tat signal peptides. In addition, in silico analysis of the full translated genome revealed a Tat candidate with a missassigned start codon. We showed that it is a new periplasmic protein in P. aeruginosa. Altogether we discovered and validated 34 Tat substrates. These show little overlap with Escherichia coli Tat substrates, and functional analysis points to a general role for the P. aeruginosa Tat system in the colonization of environmental niches and pathogenicity.